Enhanced angiotensin converting enzyme 2 regulates the insulin/Akt signalling pathway by blockade of macrophage migration inhibitory factor expression - Zhong, J-C (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: Macrophage migration inhibitory factor (MIF) is now known to be a pro-inflammatory cytokine associated with insulin resistance. Our aim was to investigate whether angiotensin converting enzyme 2 (ACE2) could modulate the expression of MIF and the insulin/Akt-endothelial nitric oxide (NO) synthase (eNOS) signalling in a human endothelial cell line (EAhy926). EXPERIMENTAL APPROACH: A recombinant plasmid encompassing human ACE2 gene was constructed and transfected into the EAhy926 cells. The mRNA, phosphorylation and protein levels of p22phox, MIF, Akt and eNOS in endothelial cells were determined by real-time PCR and Western blot analysis, respectively. KEY RESULTS: Gene transfer of ACE2 suppressed the expression of p22phox and MIF induced by angiotensin (Ang) II and Ang IV, accompanied by a decreased level of malondialdehyde in cells. In addition, Ang II diminished insulin-stimulated phosphorylation of Akt (at Ser(473)) and eNOS (at Ser(1177)) and NO generation, effects which were reversed by ACE2 gene transfer and anti-MIF treatment in endothelial cells. CONCLUSIONS AND IMPLICATIONS: The results reveal that gene transfer of ACE2 regulated Ang II-mediated impairment of insulin signalling and involved the Akt-eNOS phosphorylation pathway. These beneficial effects of ACE2 overexpression appear to result mainly from blocking MIF expression in endothelial cells, suggesting that the ACE2 gene may be a novel therapeutic target for diseases related to inflammation and insulin resistance.